Analysis of Factors Influencing Electric Vehicle Adoption with Age, Gender, and Experience as Moderating Variables Across Metropolitan, Mountainous, and Small City Regions in Indonesia - Dewi Zulfana (Journal of Social Research, 2026)
Electric vehicles (EVs) are a key strategy for achieving Indonesia's Net Zero Emissions (NZE) target by 2060. This study analyzes the factors influencing EV adoption across three regional classifications—metropolitan areas (Jakarta and Tangerang), mountainous areas (Bandung and Bogor), and small urban areas (Cirebon)—using the UTAUT2 theory (Venkatesh et al., 2012) and the partial least squares structural equation modeling (PLS-SEM) method. Data were collected from 286 respondents via an online questionnaire. The results indicate that UTAUT2 factors generally exert a significant influence, though outcomes vary across regions. In Bandung, the significant influencers of EV adoption are Facilitating Conditions (FC), Price Value (PV), and Hedonic Motivation (HM). In Tangerang, FC is the dominant factor, while in Jakarta, PV has the most significant effect. In contrast, in Bogor and Cirebon, UTAUT2 constructs do not significantly affect Use Behavior or Behavioral Intention, with an of only 12%, suggesting other dominant external factors. Furthermore, the moderation effect of experience shows that 52% of Bandung respondents have never used an EV, indicating a strong tendency among residents to accept and try new technologies, including EVs. Age moderation reveals that respondents aged 36–45 are more open to adopting new technologies. These findings underscore the need for region-specific strategies emphasizing infrastructure development, pricing, user motivation (related to design, features, and pleasurable experiences), public outreach, regulations, and performance enhancements.